Towards elimination of the dark‐rim artifact in first‐pass myocardial perfusion MRI: Removing gibbs ringing effects using optimized radial imaging. Issue 1 (12th September 2013) - Sharif, Behzad; Dharmakumar, Rohan; LaBounty, Troy; Arsanjani, Reza; Shufelt, Chrisandra; Thomson, Louise; Bairey Merz, C. Noel; Berman, Daniel S.; Li, Debiao
<x xml:space="preserve">Abstract</x> Purpose Subendocardial dark‐rim artifacts (DRAs) remain a major concern in first‐pass perfusion (FPP) myocardial MRI and may lower the diagnostic accuracy for detection of ischemia. A major source of DRAs is the "Gibbs ringing" effect. We propose an optimized radial acquisition strategy aimed at eliminating ringing‐induced DRAs in FPP. Theory and Methods By studying the underlying point spread function (PSF), we show that optimized radial sampling with a simple reconstruction method can eliminate the oscillations in the PSF that cause ringing artifacts. We conducted realistic MRI phantom experiments and in vivo studies (n = 12 healthy humans) to evaluate the artifact behavior of the proposed imaging scheme in comparison to a conventional Cartesian imaging protocol. Results Simulations and phantom experiments verified our theoretical expectations. The in vivo studies showed that optimized radial imaging is capable of significantly reducing DRAs in the early myocardial enhancement phase (during which the ringing effect is most prominent and may obscure perfusion defects) while providing similar resolution and image quality compared with conventional Cartesian imaging. Conclusion The developed technical framework and results demonstrate that, in comparison to conventional Cartesian techniques, optimized radial imaging with the proposed optimizations significantly reduces the prevalence and spatial extent of DRAs in FPP imaging. Magn Reson Med 72:124–136, 2014. © 2013 Wiley Periodicals, Inc.